256 HEMODYNAMIC CHANGES IN RESPONSE TO HYDROCORTISONE IN PRESSOR-TREATED NEONATES WITH COMPENSATED SHOCK. (1st January 2005) - Noori, S.; Friedlich, P.; Ebrahimi, M.; Wong, P.; Siassi, B.; Seri, I.
Abstract : Background: In compensated shock, blood flow (BF) to non-vital organs (kidneys, intestine, etc) is decreased to ensure normal blood pressure (BP) and BF to vital organs. Neonates requiring high doses of dopamine (DA) to maintain BP in the normal range may still be in compensated shock with ongoing non-vital organ hypoperfusion. Since low-dose hydrocortisone (HC) rapidly improves BP and decreases the need for pressor support, we wished to examine whether the HC-induced improvement in BP was associated with improved cardiac output (CO) and non-vital organ BF i.e. with resolution of both uncompensated (hypotension) and compensated (decreased non-vital organ perfusion) shock. Objective: To examine the changes in CO and vital and non-vital organ BF following HC treatment in preterm and term neonates receiving high-dose DA (± [DOB]) to maintain BP in the normal range. Methods: Neonates were eligible for enrollment if they required DA ≥15 mcg/kg/min (± DOB). Upon enrollment, patients received 2 mg/kg of HC IV x1 followed by 1 mg/kg of HC q12 hr for 4 additional doses if remained hypotensive or required DA ≥8 mcg/kg/min to maintain BP in normal range. Echocardiograms and organ (middle cerebral artery [MCA] and renal artery [RA]) BF measurements were performed prior to the first dose of HC and at 1, 2, 6-12, 24 and 48 hrs thereafter. Cardiovascular (CV) parameters measured/calculated included CO, systemic vascular resistance (SVR), myocardial performance index (MPI) and MCA and RA pulsatility index (PI). The PI is inversely related to organ BF. BP, urine output (UV), blood gasses and dose of pressors were monitored and documented throughout the study. Results: 12 patients have so far been enrolled without a patent ductus arteriosus (GA= 31.1±5.9 weeks; postnatal age= 16.9 ±15.2 days; birth weight= 1750±1086g). HC trended to increase BP, CO and SVR. Dose of DA was significantly decreased by 6-12 hours in all patients (p = 0.012). MCA PI remained unchanged while there was a trend for RA PI to decrease with the improvement in the CV status. UV increased and metabolic acidosis improved during the study. Conclusions: Maintenance of "normal" BP on medium-to-high-dose pressor/inotrope support alone may not ensure normal non-vital organ BF. HC may increase BP by increasing both CO and SVR and thus result in complete resolution of shock.